Selection of Marine Security Policyusing Fuzzy-AHP TOPSIS Hybrid Approach - Hozairi, Hozairi; Buhari, Buhari; Lumaksono, Heru; Tukan, Marcus (Knowledge Engineering and Data Science, 2019)
The research was focused on the integration of Fuzzy set theory with Analytic Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to choose the optimum maritime security policy to achieve Indonesia recognition as the world's maritime axis. The method used is AHP with fuzzy based enhancement. Here, the weight of each criterion is calculated to overcome the criticism of the scale of unbalanced rating, uncertainty, and inaccuracy in the pairwise of comparison process. The best recommendation for Indonesian maritime policies is multi task single agency which is greatly infuenced by several factors such as technology, regulations, infrastructure, economic, politic, and socio-culture. The finding shows that the hybrid approach is able to produce the best recommendation for Indonesian maritime security policy.